Analysis of thermal effect around an underground storage cavern with a combined three-dimensional indirect boundary element method. (October 2018) - Shi, Jingyu; Shen, Baotang
Abstract: This paper combines a displacement discontinuity method (DDM) for elasticity and an indirect boundary element method (IBEM) for heat conduction to investigate three dimensional thermal displacements and stresses, such as those around an underground storage cavern. The thermal displacements and stresses due to temperature change are expressed in terms of a thermal displacement potential function. For a constant point heat source, we present a derivation for solution of the thermal displacement potential function and the solution is the same as found in literature. A hybrid scheme with semi-analytical integration and a direct numerical integration are used to integrate the thermal displacement potential function due to a constant heat source on a triangular region. The hybrid scheme is used to overcome a difficulty arising with the semi-analytical integration for points whose projection on the integration plane is close to the vertices of the triangle. The combined IBEM with the hybrid integration scheme is first verified with the analytical solution for an infinite elastic body with a spherical cavity. The results agree well, although differences are observed in the early stages of simulation. Then the method is used to simulate the deformation around a liquefied natural gas underground storage cavern.